Oral history in the focus of social success formation of students - Tarasova, Tetiana Viktorivna; Necherda, Valeriia Borysivna; Kravchenko, Oksana Oleksiivna (Ustna historia w skupieniu na formowaniu pomyślności społecznej osób ubiegających się o uzyskanie wykształcenienia, 2022)
The authors consider the method of oral history including its gender aspect in the context of the potential to form the social success of modern education applicant and note its systematic use regardless of the levels and types of educational institutions and the status of higher education institutions. The scholars focus on the essence and content of the oral history method based on the analysis of interpretations of the definition «oral history» in scientific research of foreign and domestic scientists; the definition of oral history as a pedagogical method of recording by an applicant for education by means of modern technical means unique testimonies of another person on a certain topic or problem; the formation of the Ukrainian school of oral history research from information and training sessions to the Ukrainian Association of Oral History, specialized cells, preparation of special courses, cooperation between scholars and public organizations, active involvement of students and recognition of the public benefits of oral history projects by promoting participation in the competition among educational institutions in Ukraine. The authors reveal the peculiarities of implementing the method of oral history (biographical (narrative), problem (focused) in the practice of forming the social success of young students, volunteer work in public organizations; they introduce the presentation approaches to the results of oral history research: creation of radio broadcasts, exhibitions, fragments of a theatrical performance, Internet pages for museum expositions. The article proves the interrelation of social and educational function of oral history method, which helps to realize the moral and moral values of previous generations, recreate «official» historical events from the point of view of a young man or woman, get historical knowledge about the processes of the past, which is useful for methodical organization of educational process in the context of modernization of education, formation of necessary competencies and skills of education applicants in conditions of Eurointegration development of Ukraine.
Zeszyty Naukowe Collegium Witelona, nr 44(3)/2022, s. 43-54
Keywords: oral history; interview; correspondent; respondent; method; social performance of education applicants